Relationships between the front crawl stroke parameters of competitive unilateral arm amputee swimmers, with selected anthropometric characteristics - Osborough, C. D.; Payton, C. J.; Daly, D. J. (Journal of Applied Biomechanics, 2009)
The purpose of this study was to determine the relationships between swimming speed (SS), stroke length (SL), and stroke frequency (SF) for competitive single-arm amputee front crawl swimmers and assess their relationships with anthropometric characteristics. Thirteen highly trained swimmers (3 male, 10 female) were filmed underwater from a lateral view during seven increasingly faster 25-m front crawl trials. Increases in SS (above 75% of maximum SS) were achieved by a 5% increase in SF, which coincided with a 2% decrease in SL. At SSmax, interswimmer correlations showed that SF was significantly related to SS (r = .72; p < .01) whereas SL was not. Moderate but nonsignificant correlations suggested that faster swimmers did not necessarily use longer and slower strokes to swim at a common submaximal speed when compared with their slower counterparts. No correlations existed between SL and any anthropometric characteristics. Biacromial breadth, shoulder girth, and upper-arm length all significantly correlated with the SF used at SSmax. These findings imply that as a consequence of being deprived of an important propelling limb, at fast swimming speeds SF is more important than SL in influencing the performance outcome of these single-arm amputee swimmers.